Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content:• Family Stability Among Families of Children with Autism Disorder: A Social Study(An Applied Study on Families of Children with Autism Disorder in the Regions of the Kingdom of Saudi Arabia – 2023 / 1444 AH)Ms. Albatool Houmeid Almalki, Ms. Ryouf Nasser Alkhaldi, Co-Prof. Rajaa Taha Alqahtani• Mothers’ Perspectives towards Factors Associated with Children’s Screen Time: An Analytical Cross-Sectional Study in the city of JeddahMs. Ruwaydah Abdulrahman Abdulwali, Co-Prof. Najat Abdullah Malibari• Coexistence and Tolerance in Granada during the Almoravid Era (448–541 AH / 1056–1147 AD)Dr. Maali Mohammed Yasin• Challenges Hindering the Utilization of Social Innovation Programs: A Study of the Reality of Social Work Pioneers. A descriptive study of enrollees in social innovation programs at Princess Al-Anoud Foundation, Riyadh, Kingdom of Saudi Arabia - May 2025Ms. Maryam Saeed Almansouri, Co-Prof. Asma Mohammed Al-Bunyan• Researching China's policy towards the sectarian conflict in Syria and its futureDr. Lao Linging• The Crisis of Party Action in Morocco and the Challenge of Fostering Development:  An Analytical StudyDr. Fath Ellah Ramdani• The Use of Media in the Field of Da'wah: Between Reality and ProspectsCo-Prof. Muhammad Aminul Hoque• L2 Morphology Acquisition Perspectives in Optimality Theory: Preliminary Observations of The Case of the Acquisition of the Past Tense Marker “-ed”Dr. Fehmi Youssef
Keywords: Journal of Human and Social Sciences